Arthroscopic anterior cruciate ligament reconstruction with semitendinosus graft versus peroneus longus tendon graft - Kumar, Pudari Manoj; Shevte, Ishan; Phalak, Mukesh; Nair, Abhishek; ., Parth (International Journal of Research in Orthopaedics, 2020)
Background: Arthroscopic anterior cruciate ligament (ACL) reconstruction can be performed using autograft from various sources namely, bone patellar tendon graft, hamstring tendons (semitendinosus, gracilis) or peroneus longus tendon. Methods: A prospective study of 30 patients who underwent arthroscopic ACL reconstruction using quadrupled semitendinosus tendon autograft and peroneus longus tendon autograft during the study period. Results: Statistically, there is very little comparable difference between semitendinosus and peroneus longus when used for arthroscopic ACL reconstruction. However, peroneus longus tendon shows superior results when used in patients with grade 3 medial collateral ligament (MCL) injury combined with ACL injury. Conclusions: Our study brings forth the superior efficacy and quality of the double stranded peroneus longus tendon especially in cases associated with complicated injuries involving the medial collateral ligament with a follow up date of about 2 years and as a healthy supplement to other choices of autografts and revision cases.